Implementation of Interprofessional Collaboration Practice on Health Worker Satisfaction in Bali Royal Hospital - Limara Sartika Marunduh, Dian; Suprapto, Sentot Imam; Suhita, Byba Melda (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Collaboration between health workers is very important in creating synergy to provide efficient, safe, and high-quality patient services. The aim of this study was to determine the effect of the implementation of Interprofessional Collaborative Practice on the satisfaction of health workers in RSU Bali Royal Denpasar using a observational cross-sectional. His research of 138 health workers. The analyzed using ordinal regression statistical tests. The results of the value = 0.000 <0.05, on the cooperation factor is, namely p-value = 0.000 <0.05, on the coordination factor p-value = 0.000 <0.05, the partnership, cooperation and coordination factors affect the satisfaction of health workers. Partnership, coordination and cooperation the affect the satisfaction of health workers. Teamwork has a significant influence on the performance of health services in hospitals and on patient satisfaction with health care services in RSU Bali Royal Denpasar.